Outcrop Explorer: um sistema de renderização baseada em pontos para visualização e interpretação de modelos digitais de afloramento - Bellina, Gabriel Marx (Universidade do Vale do Rio dos Sinos, 2013)
The use of LIDAR-based models for geological outcrop studies has increased in the last decade, especially in the last five years. This technique has proven its potential to represent digitally tridimensional field data collected in outcrops, increasing the quality and amount of data available for interpretation by geoscientists. Under a computational point of view, researchers have found difficulty on handling the huge amount of data acquired by LIDAR system. Under a geological point of view, researchers have found difficulty to visualize efficiently the point cloud and to convert the point cloud to high-quality digital outcrop models (DOM) with specific interpretation tools. Some research groups have developed in-house software solutions in order to overcome the lack of commercial solutions. All solutions must consider the large database as the pain point of the project. Outcrop Explorer has been developed to manage large point clouds, to provide geological interpretation tools and to allow integration with geological applications through data exporting. In terms of software architecture, view-dependent level of detail (LOD) and a hierarchical space-partitioning structure in form of octree were integrated in order to optimize de data access and to promote a proper visualization and navigation in the DOM. Outcrop Explorer provides to geoscientists an editing tool capable to remove noise or unnecessary portions of the point cloud and interpretation tools as lines, plane identification and orientation e different exporting formats.
Keywords: Level of detail; Octree; Terrestrial Laser Scanner; Point clouds; OpenGL; ACCNPQ::Ciências Exatas e da Terra::Geologia